PERAN PERANGKAT DESA DALAM AKUNTABILITAS PENGELOLAAN DANA DESA - Ulfah Andriani; Tatik Zulaika (Universitas Muhammadiyah Malang, 2019)
A large budget allocation has consequences for its management which should be carried out professionally, effectively, efficiently, and accountably. Considering the amount of funds received by the villages is large and increasing every year, it is necessary role of village apparatus to assist the village head in managing the village fund. This research aims to know the role of village apparatus in accountability of village fund management in Batu Raya I village, Timang which includes Implementation, Reporting and Accountability. This research is a Descriptive Research with a Qualitative Approach that uses Primary Data and Secondary Data as the data source. The resource persons consist of Village Head, Village Secretary, Finance Chief, Chief of Development, and Treasurer. Data collection techniques were conducted with Interviews and documentation. Data analysis techniques ranging from data summarization, data presentation, and conclusions. The results of this study indicate that the Village Tool has played a role in the management of village funds and the implementation, reporting, and accountability have implemented the principle of accountability. However, there is still a need for further guidance because it is not fully in accordance with the provisions of the legislation. We recommend that the existing Village Devices in Batu Raya I Village increase their knowledge about Village Fund Management, must optimize their duties and functions and continue to maintain Accountability that has been run and built together, and the North Barito District Government should hold community development activities on financial management village and use of SISKEUDES application.